Effects of chemical leavening system and processing conditions on the opacity and other quality characteristics of whole-wheat flour tortillas. (November 2016) - Liu, Ting; Hou, Gary G.; Book, Sharon L.; Marquart, Len
Abstract: Chemical leavening is a neutralization reaction that can affect not only the opacity but also other physical and chemical properties of tortillas. Whole-wheat flour (WWF) tortillas is often associated with lack of sufficient opacity, generally considered as quality defect in tortillas. The objectives of this research were to evaluate the effects of types and amounts of leavenings (acids and base), hot press and dough temperature on the quality attributes of WWF tortillas. Three leavening acids, three levels of sodium bicarbonate (SBC) (1%, 1.5%, and 2%), hot-press temperatures of 160 °C, 177 °C, and 193 °C, and two dough temperatures (25 °C and 35 °C) were used. Sodium aluminum phosphate (SALP) produced more opaque tortillas than sodium acid pyrophosphate-28 (SAPP-28), followed by sodium aluminum sulfate (SAS). Increased amount of SBC and lower dough temperature improved opacity. Higher hot-press temperature produced lighter weight, thinner, and bigger diameter tortillas. Higher amount of SBC produced smaller, thicker, and brighter color tortillas. WWF tortillas made with SAS had the largest breaking force, while tortillas with SALP had the smallest breaking force as determined by TA-XTPlus Texture Analyzer. After 45 days of storage at room temperature, all tortillas showed decreased breaking force and extensibility. Highlights: SALP yielded most opaque WWF tortillas, followed by SAPP-28 and SAS. Higher SBC amount increased opacity, thickness and extensibility of WWF tortillas. Higher hot press temperature produced thinner and more translucent tortillas. Higher dough temperature produced tortillas with lower opacity score.